Hydrogen-Based Solutions for Enhancing Frequency Stability in Renewable Energy-Integrated Power Systems - Youngmin Jeong; Gimin Kim; Jonghoon Lee; Sangwook Han (Energies)
With the increasing adoption of renewable energy sources, such as solar and wind power, it is essential to achieve carbon neutrality. However, several shortcomings, including their intermittence, pose significant challenges to the stability of the electrical grid. This study explores hydrogen-based technologies, such as fuel cells and water electrolysis systems, as an effective solution to improve frequency stability and address the problems of power grid reliability. Using power system analysis programs, modeling and simulations performed on IEEE-25 Bus and Jeju Island systems demonstrate the potential of these technologies to mitigate reductions, reduce transmission constraints, and stabilize frequencies. The results show that hydrogen-based systems are important factors enabling sustainable energy transition.